Evaluating Teacher-made Language Tests for Assessing Upper-Secondary Students' English Proficiency - Hofman, Daniel (Univerzita Pardubice, 2024)
This thesis focuses on the creation process of teacher-made tests assessing upper-secondary students' English proficiency with a focus on grammar and vocabulary. The theoretical part researches the testing of these aspects of language, principles applied to tests, and planning and designing a test in detail to establish the foundation for the practical part. The practical part describes the way teachers prepare their tests and analyse their methods based on the insights derived from the theoretical part.
Hodnocení testů dosažené jazykové úrovně angličtiny připravených učiteli na středních školách
Keywords: testy vytvořené učiteli; gramatika; slovní zásoba; kvality testu; střední vzdělání; teacher-made tests; grammar; vocabulary; test qualities; upper-secondary education